Sistem Kerjasama dan Jaringan Perpustakaan Internasional: Studi Kasus Kerjasama Perpustakaan Indonesia-Malaysia - Yusniah Yusniah; Putri Lestari; Syafira Elvina (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The level of interest in reading in Indonesia is now very low, libraries were created to meet the needs of the community in finding information, all forms of programs were created to restore and improve people's reading, Indonesia and Malaysia publish as many as 5000 books per year, this indicates that Indonesia's population is so large but so little in their interest in reading, the library needs cooperation in developing the library, it is necessary to create a library network that can encourage people's interest in literacy. Keywords: Library Cooperation, International Library Network.